The Relationship Of Long Time Undergoing Hemodialisa And Functional Status In Chronic Kidney Failure Patients At Imelda Hospital For Indonesian Workers Medan - Gultom, Satriani H; Sagala, Deddy Sepadha Putra; Damanik, Candra Meriani; Nasution, Khoirotun Nasani (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2024)
Hemodialysis is a kidney function replacement therapy that is most often used to treat cases of chronic kidney disease. Most hemodialysis therapy procedures require 12-15 hours each week or on average the procedure is carried out 3 times a week where the implementation lasts 3-4 hours, so The length of hemodialysis therapy in patients with chronic kidney disease can cause limitations for the patient. The aim of this study was to determine the relationship between the length of time undergoing hemodialysis and the functional status of chronic kidney disease patients at the Imelda Workers Indonesia Hospital, Medan. This type of research is quantitative research with correlational methods and a cross-sectional approach design. This research was conducted in July-August 2023 in the Hemodialysis Room at the Imelda Workers Indonesia General Hospital, Medan. This research uses a probability sampling technique using the Multistage Sampling method, namely the stratified sampling method in the first stage then the simple random sampling method in the second stage, so that the total research sample is 60 respondents. The instrument used in this research is a questionnaire that refers to the Barthel Index to determine functional status. Data analysis used univariate and bivariate analysis with statistical tests (Chi Square Test) in the SPSS application. The research results in this study showed the results of the Chi-Square statistical test with a significant (p) value of 0.02 or p<0.05. The conclusion of this study is that there is a relationship between the length of time undergoing hemodialysis and the functional status of chronic kidney disease patients at the Imelda Workers Indonesia General Hospital, Medan